Strategies and social support network used by the family in care of child/adolescent with hiv/aids (Research, Society and Development, 2020)
To know the strategies and social support network of the family in the care of seropositive children / adolescents. Descriptive, exploratory and qualitative carried out in southern Brazil in 2018. Participated 20 family caregivers of HIV-positive children / adolescents. Data were collected through interviews and submitted to Content Analysis. Ethical principles were respected. Some are dedicated exclusively. They use objects to remember the medication. They prepare a varied menu and make the child / teenager help with the preparation. They check the card and consult the calendar. They guide the child / adolescent to be independent and aware. Some have no strategies. They adapt their schedules to spouses. As for the network used, one of the participants did not have it. Those who owned mentioned spouses, boyfriends, grandparents, sisters and friends. It is necessary to work with nursing through health education, so that families are instructed and prepared to deal with adversity.